Synthesis of [18F]Fluoroform with High Molar Activity. Issue 9 (25th February 2020) - Pees, Anna; Windhorst, Albert D.; Vosjan, Maria J. W. D.; Tadino, Vincent; Vugts, Danielle J.
Abstract : Fluoroform is an interesting motif for the isotopologue labelling of biologically active compounds with fluorine‐18 for PET imaging. However, so far the building block [ 18 F]fluoroform and consequently the [ 18 F]trifluoromethylated products suffered from low molar activities ranging from 0.1 to 30 GBq/µmol due to isotopic dilution under the strongly basic standard radiofluorination conditions. In this article the synthesis of high molar activity [ 18 F]fluoroform is described. By implementing a recently reported novel radiofluorination reagent, [ 18 F]triflyl fluoride, the concentration of base‐cryptand complex in the reaction could be reduced 100‐fold compared to standard radiofluorination conditions and molar activities close to 100 GBq/µmol (at end of [ 18 F]fluoroform synthesis) could be obtained, enabling the imaging of low density receptors. Furthermore, an automated procedure was developed on the commercially available NEPTIS® perform synthesizer to provide access of high molar activity [ 18 F]fluoroform to other PET centres. Abstract : The synthesis of fluorine‐18 labelled fluoroform was optimized towards high molar activities of close to 100 GBq/µmol. This was achieved by implementing a novel radiofluorination reagent, [ 18 F]triflyl fluoride, which allowed 100‐fold reduction of base and cryptand amounts in the radiofluorination reaction.